2015
DOI: 10.1557/jmr.2015.273
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of defects in nitride semiconductors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…These results are in good agreement with both theoretical predictions and experimental results [1,3,[7][8][9][10]16]. The eight XRD peaks for the bulk state in figure 8(a) and table 3 were equivalent to those of the 2H indices and corresponding d-spacings in the FFT images taken in diffraction mode from the transmission electron microscopy (TEM) measurements for the side (see figure 9(a)) and the cross-section (see figure 9(b)) of the ⃗ c axis of the grown Si needle [31][32][33][34]. The reflexes in the FFT image shown in figure 9(a) were equivalent to the spot indices and corresponding d-spacings of the (002), (110), (112), (006), and (116) 2H planes, respectively, in table 3; likewise, those shown in figure 9(b) were equivalent to the spot indices and corresponding d-spacings of the (110), (220), and (300) 2H planes in table 3.…”
Section: Lattice Parameters Of the Si Crystalmentioning
confidence: 82%
“…These results are in good agreement with both theoretical predictions and experimental results [1,3,[7][8][9][10]16]. The eight XRD peaks for the bulk state in figure 8(a) and table 3 were equivalent to those of the 2H indices and corresponding d-spacings in the FFT images taken in diffraction mode from the transmission electron microscopy (TEM) measurements for the side (see figure 9(a)) and the cross-section (see figure 9(b)) of the ⃗ c axis of the grown Si needle [31][32][33][34]. The reflexes in the FFT image shown in figure 9(a) were equivalent to the spot indices and corresponding d-spacings of the (002), (110), (112), (006), and (116) 2H planes, respectively, in table 3; likewise, those shown in figure 9(b) were equivalent to the spot indices and corresponding d-spacings of the (110), (220), and (300) 2H planes in table 3.…”
Section: Lattice Parameters Of the Si Crystalmentioning
confidence: 82%
“…This would result in higher IQE from regions of the active region with larger potential fluctuations, such as near the apex. Additionally, Tischer et al [24] simulated the strain distribution on triangular-stripes and showed that significant strain-relaxation occurs at the apex of these structures. Several other groups have also shown that nanostructures with InGaN shells exhibit significantly lower strain energy density compared to planar InGaN QWs [18,46].…”
Section: Ae Tmentioning
confidence: 99%
“…The broad emission spectrum in these nanostructures presents a unique opportunity to investigate the spectrally resolved internal quantum efficiency (IQE) and carrier dynamics across a range of wavelengths that are emitted from different areas of the nanostripe (e.g., sidewalls vs. apex). In addition, triangular nanostripes exhibit a degree of strain relaxation near the apex and a study of QW properties in this region may yield information about the effects of reduced strain on InGaN alloy uniformity and IQE in III-nitride materials [24].…”
mentioning
confidence: 99%
“…Результаты ПЭМ исследований показали, что отличительной С учетом полученных данных было сделано предположение, что наблюдавшиеся особенности спектров люминесценции могут быть описаны в рамках модели GaN с " неклассическими" квантовыми ямами, предложенной Ребане и др. [15] и позднее развитой в работе [16]. Данная модель предполагает, что ДУ в кристаллической структуре гексагонального GaN представляют собой наноразмерные гетерополитипные структуры с атомноплоскими интерфейсами, и в силу своей двумерной природы являются естественными квантовыми ямами.…”
unclassified